Biofuel from sea weed - Rachel Fran Mansa (2012)
Macroalgae or seaweed is being considered as promising feedstock for bioalcohol production due to its high polysaccharides content. Polysaccharides can be converted into fermentable sugar through acid hydrolysis pre-treatment. In this study, the potential of using carbohydrate-rich macroalgae, Gracilaria sp. as feedstock for bioalcohol production via various acid hydrolysis conditions prior to the fermentation process was done. Pre-treatment was conducted using H5SO, and HCl with molarity of 0.2M to 0.8M. The pre-treatment time were varied in the range of 15 to 30 minutes. Fermentation was conducted using Sasad, a local Sabahan fermentation agent. Alcohol extraction was done using a distillation unit. Reducing sugar analysis was done by Benedict test method. Alcohol content analysis was done using specific gravity test. After hydrolysis, it was found out that acid hydrolysis at 0.2M H-SO, and pre-treated for 20 minutes at 121C has shown the highest reducing sugar content with 10.06 mg/g yield. It was followed by hydrolyzed samples at 0.4M HCI, 30 minutes and 0.2M H+SO,, 15 minutes with yield of 8.06 mg/g and 5.75 mg/g reducing sugar content respectively. In conclusion, acid hydrolysis of Gracilaria sp. can produce higher reducing sugar yield and thus it can further enhance the bioalcohol production yield.